2022
DOI: 10.1093/gbe/evac091
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Phylogenomics of Cuscuta (Convolvulaceae) Reveals a Potentially Functional Horizontal Gene Transfer from the Host

Abstract: Horizontal gene transfers (HGTs) from host or other organisms have been reported in mitochondrial genomes of parasitic plants. Genes transferred in this fashion have usually been found non-functional. Several examples of HGT from the mitochondrial genome of parasitic Cuscuta (Convolvulaceae) to its hosts have been reported, but not vice versa. Here we used 31 protein-coding mitochondrial genes to infer the phylogeny of Cuscuta, and compared it with previous nuclear and plastid phylogenetic estimates. We also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Also, the effects of the parasitic lifestyle on mitogenome gene content of plants remain unclear, because there are so few well-annotated mitogenomes of parasitic plants. Although the mitochondrial genomes of the mistletoes Viscum (Petersen et al, 2015;Skippington et al, 2015) exhibit substantial gene loss, other parasitic plants do not show significant gene loss, including seven Orobanchaceae species (Fan et al, 2016), Cynomorium coccineum (Bellot et al, 2016), Rafflesia lagascae (Molina et al, 2014), Tolypanthus maclurei (Yu et al, 2021), Cuscuta (Lin et al, 2022), Rhopalocnemis phalloides (Yu et al, 2022), and A. indica in this study. This suggests mitochondrial gene loss may not be directly associated with the parasitic lifestyle in most parasitic plants.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the effects of the parasitic lifestyle on mitogenome gene content of plants remain unclear, because there are so few well-annotated mitogenomes of parasitic plants. Although the mitochondrial genomes of the mistletoes Viscum (Petersen et al, 2015;Skippington et al, 2015) exhibit substantial gene loss, other parasitic plants do not show significant gene loss, including seven Orobanchaceae species (Fan et al, 2016), Cynomorium coccineum (Bellot et al, 2016), Rafflesia lagascae (Molina et al, 2014), Tolypanthus maclurei (Yu et al, 2021), Cuscuta (Lin et al, 2022), Rhopalocnemis phalloides (Yu et al, 2022), and A. indica in this study. This suggests mitochondrial gene loss may not be directly associated with the parasitic lifestyle in most parasitic plants.…”
Section: Resultsmentioning
confidence: 99%
“…This occurrence is especially prevalent in higher plants, where they have incorporated several plastid sequences from neighboring chloroplasts. This evolutionary process has transpired over an extended timeframe and is likely ongoing ( Choi and Park, 2021 ; Garcia et al., 2021 ; Lin et al., 2022 ). Currently, the availability of mitogenome resources for the plants is limited.…”
Section: Introductionmentioning
confidence: 99%
“… Vogel et al (2018) reported a high confidence set of 64 genes that were acquired by C. campestris from other plants by HGT, while Yang et al (2019) identified 108 probably functional HGTs in the same species (some of those shared with root parasitic Orobanchaceae) in addition to 42 host transposon-derived transfers. A horizontally transferred miRNA in the nuclear genome of C. campestris ( Zangishei et al , 2022 ) as well as a functional HGT into the mitochondrial genome were recently described ( Lin et al , 2022 ). Once both quality and quantity of the genomic resources in Cuscuta is improved, our understanding of the mechanisms as well as the functional significance of HGT will be increased and should reveal the fundamental evolutionary processes underlying the transition to parasitism.…”
Section: Introductionmentioning
confidence: 99%